Óleo essencial e ácidos orgânicos na alimentação de frangos de corte: desempenho e qualidade intestinal - Bochio, Vivielle (2019)
A study was carried out to evaluate the effects of the use of organic acids and essential oils in comparison to antibiotics in broilers feeding, comparing performance (mean weight, weight gain, feed intake, feed conversion), carcass yield, and intestinal quality in the period of 42 days. A total of 336 male chicks of 1 day old were distributed in 4 treatments with 6 replicates each, being: control treatment with antibiotic growth promoter based on enramycin, treatment with organic acids, treatment with essential oil and another with the association of essential oils and organic acids. The essential oil consists of encapsulated microparticles containing a standardized combination of three substances: natural pepper extract (Capsicum spp: capsaicin), together with active substances identical to the natural one of oregano (Origanum vulgare: carvacrol) and cinnamon (Cinnamomum spp .: cinnamaldehyde), at concentrations: 4.6% carvacrol, 2.6% cinnamaldehyde and 2.0% capsaicin, and organic acid composed basically of medium chain fatty acids (lauric acid and monolaurate). The diets were based on corn and soybeans. The design was completely randomized. Data were submitted to analysis of variance ANOVA and the means were compared by Tukey test at the 5% level of significance. The results showed no statistical difference between the control treatment with antibiotic growth promoter, treatment with organic acids and treatment with essential oils. However, a significant difference was observed in the treatment 4 with association of organic acids and essential oils in comparison to the other treatments in all the periods of the study, locomotor problems were also observed at the beginning of the second week of the experiment in the treatment 4 with the association of organic acids and essential oils. In the results of carcass yield and intestinal morphometry there was no significant difference between the 4 treatments. It is concluded that the organic acids and essential oils used individually demonstrate performance efficacy, carcass yield and intestinal morphometry, and may be a tool in replacing growth promoting antibiotics.